2013
DOI: 10.1104/pp.113.225524
|View full text |Cite
|
Sign up to set email alerts
|

Selected Reaction Monitoring to Determine Protein Abundance in Arabidopsis Using the Arabidopsis Proteotypic Predictor

Abstract: In reverse genetic knockout (KO) studies that aim to assign function to specific genes, confirming the reduction in abundance of the encoded protein will often aid the link between genotype and phenotype. However, measuring specific protein abundance is particularly difficult in plant research, where only a limited number of antibodies are available. This problem is enhanced when studying gene families or different proteins derived from the same gene (isoforms), as many antibodies cross react with more than on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…The mass spectrometer was run in positive ion mode, and for each parent/transition, the fragmentor was set to 130, dwell time was 5 ms, and collision energy was 22.9 V for LVELLPEN-SLAIISSAPVK and 23.99 V for YTNLDDFQNSASLGK. Detailed information for parent ions, transition, and collision energy for peptides (FSYNGQPAEIK, ILDWENTSTK, and GVISEDFNSYGSR) from tricarboxylic acid cycle enzyme aconitase2 (At4g26970) that was used as a control has already been reported (Taylor et al, 2014). Selected reaction monitoring chromatograms were analyzed in MassHunter Workstation Quantitative Analysis (version B.04.00, build 4.0.225.0; Agilent Technologies), and quantitative results were obtained by integrating the area under the peak of each quantifier transition.…”
Section: Isolation Of Mitochondria From Hydroponic Plants Using Gradimentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometer was run in positive ion mode, and for each parent/transition, the fragmentor was set to 130, dwell time was 5 ms, and collision energy was 22.9 V for LVELLPEN-SLAIISSAPVK and 23.99 V for YTNLDDFQNSASLGK. Detailed information for parent ions, transition, and collision energy for peptides (FSYNGQPAEIK, ILDWENTSTK, and GVISEDFNSYGSR) from tricarboxylic acid cycle enzyme aconitase2 (At4g26970) that was used as a control has already been reported (Taylor et al, 2014). Selected reaction monitoring chromatograms were analyzed in MassHunter Workstation Quantitative Analysis (version B.04.00, build 4.0.225.0; Agilent Technologies), and quantitative results were obtained by integrating the area under the peak of each quantifier transition.…”
Section: Isolation Of Mitochondria From Hydroponic Plants Using Gradimentioning
confidence: 99%
“…2A). Peptides from mitochondrial aconitase were used as a control for mitochondrial protein (Taylor et al, 2014). Quantification of ICP55 peptides in trypsin-digested whole mitochondria showed that both peptides 1 and 2 were not detectable in icp55 when compared with the wild type (Fig.…”
Section: Subcellular Localization Sequence Similarity and Expression mentioning
confidence: 99%
“…Moreover, since sPEPs often occur at low abundance (Hanada et al, 2013;Andrews and Rothnagel, 2014) and classical proteomic analyses involving data-dependent acquisition mass spectrometry have a bias for highly abundant peptides, they have limited potential to detect sPEPs. Targeted proteomic techniques as dataindependent acquisition mass spectrometry and selected/multiple reaction monitoring could be promising in this regard for detection of specific sPEPs though less suitable for discovery-based applications (Samir and Link, 2011;Chen et al, 2014;Doerr, 2014;Taylor et al, 2014). Finally, it should be noted that in planta identification of a peptide does not necessarily imply that it fulfills any biological role but the peptide can instead be part of suggested translational noise (Guttman and Rinn, 2012).…”
Section: Peptides Encoded By Sorfs In Primary Transcripts Of Mirnasmentioning
confidence: 99%
“…Recently, to measure high accurate protein abundances, SRM analysis has been applied to the field of plant science. [19][20][21][22] Lehmann and colleagues have successfully quantified the abundance of four sucrose-phosphate synthase and Tubulin4 (TUB4) transcripts were amplified by PCR in Col-0, pdr9/abcg37-1, pdr9/abcg37-2, and pdr9/abcg37-3 roots grown on basal medium. PDR9/ABCG37 transcript was amplified using primer F1 and R1 for 28 PCR cycles and with primer F1 and R2 for 35 PCR cycles.…”
Section: Determination Of Expression Levels In Mutant Lines By Srm Anmentioning
confidence: 99%
“…Absolute quantification by the SRM analysis Col-0 and pdr9/abcg37 mutants were vertically grown on basal medium or Zn0 medium for 10 days at 22 C under 16-h light/8-h dark conditions. In total, 1,200 seeds were grown on basal, 0-Zn, 0-Mn or 0-Fe medium.…”
Section: Rna Extraction and Quantitative Real Time (Rt)-pcrmentioning
confidence: 99%